Cloud Resource Cost Minimization using PSO Algorithm - Thakur, Garima Singh; Choudhary, Sapna (International Journal of Computer Sciences and Engineering, 2025)
In the current scenario, Cloud computing carved itself as an emerging technology which enables the organization to utilize hardware, software and applications without any upfront cost over the internet. A very efficient computing environment is provided by cloud computing where the customers or several tenants are in need of multiple resources to be provided as a service over the internet. The challenge before the cloud service provider is, how efficiently and effectively the underlying computing resources like virtual machines, network, storage units, and bandwidth etc. should be managed so that no computing device is in under-utilization or over-utilization state in a dynamic environment. A good task scheduling technique is always required for the dynamic allocation of the task to avoid such a situation. A Particle Swarm Optimization (PSO) package is integrated in our simulator so as to achieve an effective result where PSO will randomly find the suitable Physical host in heterogeneous environment so as to transfer the load. Through this paper we are going to present the new Algorithm based on task scheduling technique, which will distribute the load effectively among the virtual machine so that the overall cost should be minimal. A comparison of this proposed Algorithm is performed on our simulator which shows that, this will outperform the existing techniques like EFT.